The electroencephalography of chronically headache patients in Sardjito General Hospital, Yogyakarta - Sri Sutarni, Sri Sutarni (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1990)
One hundred seventy four cases of 9 - 63 year old patients with chronical headache were reported. One hundred and twelve cases (64.37%) were examined by electroencephalography from April 1, 1986 to March 31, 1987, The EEG of 51 (29.31%) patients were normal, 44 (25.29%) with irritation pattern and 17 (9.77%) with hypofunction.It is suggested that the irritation pattern in chronical headache needed more attention in order to know the etiology and the location of intracranial lesion.Key Words: chronical headache - electroencephalography - irritation pattern - intracranial lesion - slow wave focus